2002
DOI: 10.2166/wst.2002.0604
|View full text |Cite
|
Sign up to set email alerts
|

MBR-technology in municipal wastewater treatment: challenging the traditional treatment technologies

Abstract: In the Netherlands a development programme for the application of the MBR technology in municipal wastewater treatment has started. This paper briefly describes this development programme and goes into detail for the first step: a large pilot plant study at the Beverwijk WWTP. Under the supervision of DHV Water four different membrane systems from Kubota, Mitsubishi, X-Flow and Zenon were extensively tested. The objectives set for the study were more than achieved. The available world knowledge regarding munic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Advanced membrane bioreactors (MBRs), a combination of the conventional activated sludge process (ASP) and MF/UF membrane separation, have been increasingly attractive for reclamation of municipal wastewater because of advantages of small foot print, reduced sludge production and consistently high quality of effluent in treatment of domestic sewage over ASP [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced membrane bioreactors (MBRs), a combination of the conventional activated sludge process (ASP) and MF/UF membrane separation, have been increasingly attractive for reclamation of municipal wastewater because of advantages of small foot print, reduced sludge production and consistently high quality of effluent in treatment of domestic sewage over ASP [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to recent technical innovations and significant cost reductions of especially the employed membranes, the applicability of MBR technology for wastewater treatment of both industrial and domestic has sharply increased. 201 MBR are characterized by high biomass concentrations, low sludge production, low F/M ratios, and long SRT, which are all beneficial for the treatment of highly variable industrial wastewaters. Unlike in biofilm reactors, the biomass will be mainly present in the suspended or flocculent form, which likely does not lead to the formation of significant pH or substrate gradients into the biomass.…”
Section: Bioreactor Considerations For the Treatment Of Highly Variabmentioning
confidence: 99%
“…The most simple configuration is based on a conventional activated sludge plant in which the sedimentation tanks are replaced by membrane filtration, either internally in the bioreactor or externally in separated tanks (see Figures 3A and 3B). 89,201 In another configuration, the membrane separates the biomedium from the wastewater by an extractive membrane (see Figure 3C), that is, the pollutants diffuse from the wastewater through the membrane into a biomedium containing microorganisms. 134−136 Because the biomass is physically separated from the wastewater, extreme environmental characteristics of the wastewater such as high pH and salinity principally do not affect the microbial activity in the biomedium.…”
Section: Bioreactor Considerations For the Treatment Of Highly Variabmentioning
confidence: 99%
“…Membrane bioreactor (MBR) technology today has become a robust technology and is attractive in reclamation of domestic sewage due to its advantages of consistently high quality of effluent, smaller footprint, reduced sludge production and simple system operation and facility management over the conventional activated sludge process (ASP) (Fan et al 1996;Ghyoot & Verstraete 1999;Gander et al 2000;Holler & Trosch 2001;Stephenson et al 2001;Lawrence et al 2002;Roest et al 2002;Lee et al 2003;Yoon et al 2004;Tao et al 2005;Trussell et al 2005;Judd 2006; Qin et al 2006a;Qin et al 2006b;Fletcher et al 2007;Oo et al 2007). Gander et al (2000) compared various MBRs for domestic wastewater treatment with cost considerations and concluded that the submerged configuration with withdrawing the permeate from the outside to inside of membranes would be more cost effective in operation than the side-stream configuration with water being pressured from the inside to outside of membranes.…”
Section: Introductionmentioning
confidence: 99%